'For the bibliographers at UCL': A humument and the lessons it teaches 21st century librarians1. (20th September 2016) - Welsh, Anne
Abstract : Object-based learning lies at the heart of teaching in both historical bibliography and cataloguing classes on the MA Library and Information Studies at UCL. Tom Phillips's work A humument and the novel he chose to use as his canvas, W.H. Mallock's A human document provide memorable 'object lessons' with scope for students to synthesize and evaluate their pre-existing learning from inside and outside the modules. It is important that the examples used in class are simple enough to illustrate the strengths of any conceptual model yet complex enough to highlight its limits. It is also ideal if examples can be beautiful as well as useful. A humument fulfills all these criteria and, for students with no background in art or art librarianship, also introduces the artists' book as a genre and artists themselves as an important and interesting user group within information services.